Antimicrobial and Other Biomedical Properties of Extracts from Plantago major, Plantaginaceae - Kairat Zhakipbekov; Aknur Turgumbayeva; Raushan Issayeva; Aliya Kipchakbayeva; Gulnara Kadyrbayeva; Meruyert Tleubayeva; Tamila Akhayeva; Kuanysh Tastambek; Gaukhar Sainova; Elmira Serikbayeva; Karakoz Tolenova; Balzhan Makhatova; et al. (MDPI AG, 2023)
Since ancient times, many scientists and doctors have used various herbs to treat diseases. Conventional drugs often have side effects, and pathogens are becoming resistant to these types of drugs. In such circumstances, the study of traditional medicinal plants is an effective and logical strategy for finding new herbal medicines. One such herb is Plantago major, a perennial plant in the Plantaginaceae family that is found throughout the world. The Plantago major plant has been used as a medicine for the treatment of various diseases. Studies have shown that plant extracts of Plantago major exhibit antimicrobial, antiviral, and anti-inflammatory effects, and have wound-healing properties. This review collects and presents the results of various studies of Plantago major plant extracts with antimicrobial, antiviral, antifungal, anti-inflammatory, and wound-healing properties, which demonstrate a wide range of therapeutic possibilities of Plantago major plant extracts and have a huge potential for use as a medicinal raw material.